Effects of Safety-Related Alerts on Aliskiren Use Trends: An Observational Study from Portugal - Teixeira Rodrigues, António (2014)
Drug safety profile is not fully known before marketing authorization and the publication of aliskiren safety-related alerts (SA) could have clinical and economic consequences. This study sought to assess the impact of aliskiren SA on consumption trends of all medicines containing aliskiren available in Portugal.